2015
DOI: 10.1158/1535-7163.mct-15-0206
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Neurokinin-1 Receptor Compromises Canonical Wnt Signaling in Hepatoblastoma

Abstract: The substance P (SP)/NK-1 receptor (NK1R) complex represents an intriguing anticancer target for a variety of tumors, including hepatoblastoma (HB). Therefore, NK1R antagonists, such as the clinical drug aprepitant, recently have been proposed as potent anticancer agents. However, very little is known regarding the molecular basis of NK1R inhibition in cancer. Using reverse phase protein array, Western blot, Super TOP/FOP, confocal microscopy, and sphere formation ability (SFA) assays, we identified the AKT an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…Henssen et al reported that NK1R inhibition in neuroblastoma repressed E2F2 and induced TP53 signaling, and that this effect may be in part due to activation of SRC (26). In a recent publication regarding the downstream signaling following NK1R inhibition in hepatoblastoma, we found potent inhibition of the AKT/mTor pathway, with subsequent strong inhibition of 4E-BP1/2 and p70S6K, both downstream members of the AKT pathway (25).…”
Section: Therapeutic Innovations In Neuroblastomasupporting
confidence: 54%
See 3 more Smart Citations
“…Henssen et al reported that NK1R inhibition in neuroblastoma repressed E2F2 and induced TP53 signaling, and that this effect may be in part due to activation of SRC (26). In a recent publication regarding the downstream signaling following NK1R inhibition in hepatoblastoma, we found potent inhibition of the AKT/mTor pathway, with subsequent strong inhibition of 4E-BP1/2 and p70S6K, both downstream members of the AKT pathway (25).…”
Section: Therapeutic Innovations In Neuroblastomasupporting
confidence: 54%
“…There is now accumulating evidence for hepatoblastoma that NK1R may be highly expressed in CSCs of that tumor and can be readily targeted with NK1R antagonists. For example, our data show that the application of NK1R antagonists not only diminished the sphere-formation capacity of hepatoblastoma cells, but also decreased the expression of liver-specific CSC markers and selected ESC genes (25). Importantly, liver specific CSCs could be successfully targeted with NK1R antagonists such as aprepitant.…”
Section: Therapeutic Innovations In Neuroblastomamentioning
confidence: 81%
See 2 more Smart Citations
“…Recently, our group was able to describe the downstream mechanisms following inhibition of NK1R by aprepitant on hepatoblastoma cells (107). First, a robust inhibition of 4EBP1 and p70S6K was identified, which are both downstream members of the PI3K/AKT/mTOR pathway.…”
Section: Downstream Mechanisms Following Inhibition Of Hepatoblastomamentioning
confidence: 99%